Generalization of Lohwater-Pommerenke's theorem - Dovbush, Piotr Vasilievich (Mathematica Montisnigri, 2023)
In this paper, as an application of Zalcman's lemma in ℂn, we give a sufficient condition for normality of holomorphic functions of several complex variables, which generalizes previous known one-dimensional criterion of A.J. Lohwater and Ch. Pommerenke.